LGBT IN RECENT TIMES MALAYSIA: EXPLORING THE VIEWS OF THE DIFFERENT SEGMENTS OF MALAYSIAN SOCIETY - Jerome, Collin; Ting, Su Hie; Jacinta Jiin-Yih, Yeo; Ling, Hsin Nie (2021)
The past few years have witnessed a growing acceptance and inclusion afforded to members of the LGBT communities by Malaysian society. However, much more needs to be known about the degree of acceptance and inclusion as demonstrated by the various segments of society. The present study examined this knowledge gap by exploring the discrepant views of LGBT and non-LGBT individuals on societal receptivity towards the LGBT phenomenon in present-day Malaysia. The findings revealed that the participants held different views about the phenomenon ranging from accepting and rejecting LGBT for several reasons including religion, gender roles, and norms, cultural practices, and values of ethnic groups. The findings also revealed that individual differences and cultural influences altered the conditions of or for the participants' views about the phenomenon, which in turn influenced them to either accept or reject LGBT. The findings suggest the need to consider the various segments of Malaysian society who may have differing views and expectations about the LGBT phenomenon to better understand the changing realities affecting the lives of their fellow LGBT members.